Enterobius Vermicularis Infection: Prevalence and Risk Factors Among Primary School Children in Al-mudhafar Directorate, Taiz, Republic of Yemen - Waheed A. M. Ali (Enhanced Knowledge in Sciences and Technology, 2022)
Enterobius vermicularis (pinworm) is a common parasitic infection, especially in children; it causes gastrointestinal disease called enterobiasis. The present study was aimed to explore the prevalence, and the associated risk factors of this infection, among the students of the primary schools in Al-Mudhfar directorate, Taiz, Republic of Yemen. A cross-sectional study conducted on 370 of the primary school children (4-12 years). The perianal cellophane tape method was used to investigate pinwom infection. Parents were asked to complete questionnaires to collect information about children and families personal and hygienic characteristics. The overall prevalence rate of Enterobius vermicularis infection was 68%. It is found that there is no association between the prevalence and the gender or the age of the participants. Parent’s educational level (P < 0.05), Family income levels (P = 0.074) and hosing levels (P = 0.037), all were found to be risk factors for pinworm infection. Personal hygiene factors that had found to affect the prevalence of infection of this worm were, hand washing after using toilet (P = 0.001), scratching around the anus (P = 0.001), Finger’s sucking or nail’s biting (P = 0.07), and exposing bedspreads to sunlight (P = 0.01). The rate of pinworm (Enterobius vermicularis) infection among the primary school children in Taiz; Republic of Yemen is high, and, therefore, represent an important parasitic disease. Waste disposal and good sanitation, in addition to mass screening for preschool and school children in Taiz governorate, and if possible in the whole country should be admitted. Pinworm infection among school children in Taiz is high, good sanitation and insurance of unpolluted food and water supplies, in addition to mass screening and treatment of infected persons should be admitted for the population of Taiz City to decrease the rate of pinworm infection.